Volume of Enlarged White Matter of Thalamus among Individuals with Depression on Magnetic Resonance Image: A Study of BrainSuite Segmentation - Alarifi Abdulaziz; Taha Khalid M; Elamin Abubaker Y; Almasaad Juman M; Bakhit Nagi M (Wolters Kluwer Medknow Publications, 2024)
BackgroundThe thalamus, located in the diencephalon, regulates emotions and memories. If there is a problem in this area of the brain, it can cause an amnestic syndrome characterized by difficulties in remembering and recognizing things. The objective of this study was to identify changes in the volume of the thalamus while contrasting them among individuals with depression. Materials and MethodsThe study involved measuring the volumes of the white matter of the thalamus in 79 patients with depression (42 males and 37 females) between 20 and 40 years (24 ± 5.51). This was compared to a control group of 53 individuals (24 ± 4.91) consisting of 29 males and 24 females, who were comparable in terms of sex and age. The measurements were taken employing BrainSuite version 18a. 021 Win 64bit software on a Philips 1.5 Tesla Magnetom Avanto Vision System magnetic resonance imaging (MRI). The Magnetization Prepared Rapid Acquisition (MPRA) was utilized to acquire three-dimensional images with T1 weighting. ResultsThe volume of white matter in the respective right and left thalamus was 5.09 cm3 and 4.58 cm3 (±standard deviation (SD) = 6.43 and 4.74) among individuals with depression. In the control group, the volume of white matter in the right and left thalamus was 3.66 cm3 and 4.16 cm3 (±SD = 3.99 and 5.06), respectively. The P-value is more than 0.05. The average volume of white matter in the right and left thalamus of females with depression and controls was 6.47 cm3 and 6.77 cm3 (with SD of 4.17 and 4.3), and 3.25 cm3 and 3.13 cm3 (with SD of 6.55 and 6.77), respectively. ConclusionsOur data suggest that individuals with depression exhibit an augmentation in the white matter of the thalamus, particularly in female patients where there is an upsurge in white matter volume. Depression appears to be linked to a decrease in volume on the left side of the brain.